2010
DOI: 10.1186/1471-2415-10-27
|View full text |Cite
|
Sign up to set email alerts
|

Expression of connexin genes in the human retina

Abstract: BackgroundGap junction channels allow direct metabolically and electrical coupling between adjacent cells in various mammalian tissues. Each channel is composed of 12 protein subunits, termed connexins (Cx). In the mouse retina, Cx43 could be localized mostly between astroglial cells whereas expression of Cx36, Cx45 and Cx57 genes has been detected in different neuronal subtypes. In the human retina, however, the expression pattern of connexin genes is largely unknown.MethodsNorthern blot hybridizations, RT-PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…Gap junctions are formed by a variety of connexins, but CX36 is perhaps the most important, particularly for transmission of the rod signal. 27,33,34 To our knowledge, this is the first report of CX36 expression in retinal progeny of human pluripotent stem cell cultures; however, the sparse distribution of CX36 plaques on RECOV-ERIN+ photoreceptor-like cells suggests that further maturation and/or changes in culture conditions are needed to fully promote gap junction formation in vitro. Even so, these data suggest that TiPSC-OV cultures may be useful for studying synapse development and/or generating donor retinal neurons capable of communicating with host cells following transplantation into the subretinal space.…”
Section: Discussionmentioning
confidence: 70%
“…Gap junctions are formed by a variety of connexins, but CX36 is perhaps the most important, particularly for transmission of the rod signal. 27,33,34 To our knowledge, this is the first report of CX36 expression in retinal progeny of human pluripotent stem cell cultures; however, the sparse distribution of CX36 plaques on RECOV-ERIN+ photoreceptor-like cells suggests that further maturation and/or changes in culture conditions are needed to fully promote gap junction formation in vitro. Even so, these data suggest that TiPSC-OV cultures may be useful for studying synapse development and/or generating donor retinal neurons capable of communicating with host cells following transplantation into the subretinal space.…”
Section: Discussionmentioning
confidence: 70%
“…It has been shown that the human retina, similar to those of other mammalian species, expresses Cx36 both in the IPL and OPL (Söhl et al 2010), and the distribution of immunostained plaques resembled patterns found previously in the mouse, rabbit, rat and the monkey Mills et al 2001;Deans et al 2002;Kihara et al 2006Kihara et al , 2010O'Brien et al 2012;Kovács-Ö ller et al 2014). However, it has been difficult to obtain details on the GJ forming neurons of the human retina due to the postmortem decomposition of available tissue.…”
Section: Introductionmentioning
confidence: 57%
“…Cones have been shown to express Cx36 in various mammals including the monkey, rabbit, mouse, guinea pig (Raviola and Gilula 1973;Deans et al 2002;Feigenspan et al 2004;Lee et al 2003;O'Brien et al 2012) and humans (Söhl et al 2010). Some of these contacts have been shown to be functional GJs that allow for the electrical and tracer coupling of nearby cones (Schneeweis and Schnapf 1999;Li and DeVries 2004).…”
Section: Cx36 Gjs Mediate Photoreceptor Couplingmentioning
confidence: 98%
“…Nevertheless, the precise mechanisms mediating the transduction of this defocus signal leading to myopia are still unclear. GJD2 is reportedly localized at the synapses between alpha-ganglion cells, AII amacrine cells, cone bipolar cells and photoreceptor cells [42][43][44][45][46][47][48][49][50][51] . Of all the interactions between these cells, the coupling between the amacrine cells and ganglion cells has been reported to be dramatically reduced in GJD2 knockout mice 52 .…”
Section: Discussionmentioning
confidence: 99%